2014
DOI: 10.1038/ki.2013.473
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease reduces muscle mitochondria and exercise endurance and its exacerbation by dietary protein through inactivation of pyruvate dehydrogenase

Abstract: Chronic kidney disease impairs physical performance. Here the time course and mechanism of muscle insufficiency in renal failure and the influence of dietary protein were studied using 5/6 nephrectomized C57Bl/6 mice, focusing on muscle mass and mitochondria. A decrease in muscle mitochondria and running distance was found in young (16-20 weeks) 5/6 nephrectomized mice, despite the preservation of muscle volume and power. However, a decrease in muscle volume, associated with a reduction in muscle power, was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
155
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(164 citation statements)
references
References 40 publications
7
155
2
Order By: Relevance
“…Increased oxidative stress and inflammatory cytokines decrease mitochondria function 6. The present study revealed that IS decreases the expression of PGC‐1α (mitochondrial biosynthesis‐related factor) and increases autophagy (mitochondrial degradation‐related factor) in skeletal muscle in both in vivo and in vitro experiments.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Increased oxidative stress and inflammatory cytokines decrease mitochondria function 6. The present study revealed that IS decreases the expression of PGC‐1α (mitochondrial biosynthesis‐related factor) and increases autophagy (mitochondrial degradation‐related factor) in skeletal muscle in both in vivo and in vitro experiments.…”
Section: Discussionsupporting
confidence: 50%
“…Previous reports and our in vitro experiments ( Figure 1) demonstrated that there is mutual relationship between exercise capacity in treadmill experiments and muscular mitochondrial function 6, 9, 10, 19. We therefore further evaluated the mitochondrial status in skeletal muscle of CKD mice.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In a rat model with chronic cyclosporin A (CsA) treatment, mitochondrial DNA copy number, along with the expression of nuclear and mitochondrial DNA-encoded oxidative phosphorylation (OXPHOS) proteins, peroxisome proliferator-activated receptor-γ coactivator (PGC)-1α, and mitochondrial transcription factor-A (Tfam) was dramatically decreased [87]. Interestingly, in a mouse model with 5/6 nephrectomy, decreases of mitochondrial content also happened in muscles, which resulted in impaired exercise endurance, a well-documented feature in chronic kidney diseases [88]. Mitochondrial biogenesis increases the mitochondrial mass and functional capacity or helps preserve it by replacing damaged mitochondria, so defects in mitochondrial biogenesis may deteriorate kidney injury.…”
Section: Mitochondrial Pathology In Kidney Diseasesmentioning
confidence: 99%